La producción del cine fronterizo: Una industria de sueño - Norma Iglesias (Estudios sobre las Culturas Contemporáneas)
In this essay, the author analyses borderline cinema from the point of view of its production. In order to do so, she uses a series of interviews on the origins of the borderline cinema, production at the present time, themes to be treated, producers, companies, etc. The inteviewees are three producers who give existence to this genre. A general criticism is made of the type of cinema that has been produced at the borderline in the last feVv decades, and of the commercial ends and meanings given to the borderline theme which do not consider the possibilities of this medium -as a cultural product- to become an informal means of education.